2019
DOI: 10.1038/s41598-019-45854-0
|View full text |Cite
|
Sign up to set email alerts
|

The decline of farmland birds in Spain is strongly associated to the loss of fallowland

Abstract: Farmland bird populations have strongly declined across Europe over the last decades due to agriculture intensification, despite successive reforms of EU’s Common Agricultural Policy (CAP). In parallel, CAP has led to a reduction of fallow land, a critical habitat for biodiversity in agroecosystems. Fallow land in Spain, a country harboring the largest European populations of many endangered farmland birds, has decreased by 1.1 million ha in 15 years. The significant positive relationship between yearly change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 25 publications
9
81
0
Order By: Relevance
“…Negative effects of increasing maize cultivation on farmland bird diversity in Germany are also identified by Sauerbrei et al (2014). The loss of fallow land is likely to affect farmland bird species via the loss of habitat for breeding birds, as well as the loss of valuable food sources for granivorous sedentary birds and partial migrants during winter (Henderson and Evans 2000, Sudfeldt et al 2009, Traba and Morales 2019. Moreover, insect abundance is likely to be much higher on fallow land than on cultivated field blocks (Traba and Morales 2019), e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative effects of increasing maize cultivation on farmland bird diversity in Germany are also identified by Sauerbrei et al (2014). The loss of fallow land is likely to affect farmland bird species via the loss of habitat for breeding birds, as well as the loss of valuable food sources for granivorous sedentary birds and partial migrants during winter (Henderson and Evans 2000, Sudfeldt et al 2009, Traba and Morales 2019. Moreover, insect abundance is likely to be much higher on fallow land than on cultivated field blocks (Traba and Morales 2019), e.g.…”
Section: Discussionmentioning
confidence: 99%
“…because it is not treated with insecticides and accordingly the loss of fallow land may also reduce food availability for insectivorous species. Studies from other European countries also identified fallow land as one of the most important habitats in agricultural landscapes, particularly for farmland birds (Traba and Morales 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be necessary to define suitable ecological indicators reflecting the improvement in biodiversity or ecosystem services arising from the environmental practices put in place. The effects of managements should be evaluated on particular species of conservation concern and using global measures, such as the farmland bird index, able to effectively document the health state and trends of bird communities (Traba & Morales, ). It would be equally necessary to set efficient control measures to ensure compliance on conditionality, as these are basic statutory requirements.…”
Section: A New Opportunity To Change the Fallow Paradigmmentioning
confidence: 99%
“…Results from the Pan‐European Common Bird Monitoring Scheme for 39 common farmland birds monitored between 1980 and 2015 show that this bird group is undergoing the steepest population declines, with a regressive trend of −55% (PECBM: http://www.ebcc.info/european-wild-bird-indicators-2017-update/). The loss of landscape heterogeneity and the disappearance of semi‐natural vegetation types, such as field margins and fallow land, are key drivers of farmland bird decline (Benton, Vickery, & Wilson, ; Traba & Morales, ).…”
Section: Introductionmentioning
confidence: 99%